THE INFLUENCE OF BRAND IMAGE AND PRODUCT QUALITY ON PURCHASING DECISIONS FOR HONDA MOTORCYCLES AT PT ASTRA MOTOR CENTRAL JAVA - Syafa Libelia Alfiana; Sri Nawatmi (Universitas Nusa Cendana, 2026)
This study aims to gain a deeper understanding of the relationship between brand reputation and perceived product quality with consumer decision-making behavior in purchasing Honda motorcycles, particularly in the operational area of PT Astra Motor Central Java. The strategy used is quantitative, with a survey method as the data collection instrument. Respondents were selected purposively, namely individuals who empirically have experience purchasing Honda motorcycles. Data collected through questionnaires were then analyzed using multiple linear regression. The results of the analysis indicate that brand reputation and perceived product quality have a positive influence on consumer decision-making behavior in purchasing. This study confirms that brand symbolism in the minds of consumers and perceptions of product quality are factors that strengthen individual tendencies to make purchases. Thus, companies are advised to consistently build and maintain a positive brand reputation and maintain product quality, not only as an economic strategy, but also as an effort to form and maintain relationships with consumers that have implications for long-term loyalty. Keywords: Brand Image; Product Quality; Purchase Decision